Dustborn - Bowman, Erin (Houghton Mifflin Harcourt, 2021)
"When raiders sent by a man known as the General attack her village, Delta suspects he is searching for her. Delta sets out to rescue her family but quickly learns that in the Wastes no one can be trusted; perhaps not even her childhood friend, Asher, who has been missing for nearly a decade. If Delta can trust Asher, she just might decode the map and trade evidence of the Verdant to the General for her family. What Delta doesn't count on is what waits at the Verdant: a long-forgotten secret that will shake the foundation of her entire world"--